The current maturity level and potential implications of the blockchain-based trade financing process : Qualitative research in the Finnish banking sector - Aaltonen, Oona (My University, 2021)
A profound disruption in various industries by the nature of decentralized blockchain technology has been inevitably witnessed ever since the publication of Satoshi Nakamoto’s (2008) whitepaper introducing the concept of bitcoin and its underlying technology blockchain. The financial sector has been in the front-line of this aforementioned disruption and initiatives have been established to deploy the technology within the trade finance sector to ameliorate the rather obsolete economical hurdles of today’s economy. The aim of the research is to outline the maturity level of the blockchain-based trade financing and the potential implications to the banks and its clients as well as the implications to the Finnish banking sector. The empirical research is conducted by interviewing 4 professionals from different banks and 2 blockchain technology professionals. The research yields comprehensive results through observation of previous literature in conjunction with 6 held interviews with blockchain and banking professionals. The research finds that the blockchain technology is still quite immature and the main demerits constraining the development are mainly in the environmental aspect such as market approval and regulatory environment. However, the research finds that the blockchain technology suits well to the trade financing. The research additionally finds that the blockchain technology can mitigate the traditional risks associated with the trade finance process which enables the banks to provide financing with lower barriers. This particularly effects SMEs which have previously had difficulties in accessing affordable financing. Further, there are competitive implications to the market caused by the blockchain-based trade financing platforms currently being developed. The research finds that although Finnish banks are involved in blockchain-based projects, attitudes towards blockchain technology are reserved. In addition, stable market acceptance and legislation are needed for large-scale use of the technology.
Keywords: Blockchain, Trade Financing, Financial Sector